2011
DOI: 10.1021/nn203012q
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Single Enzymatic Events in Rare or Single Cells Using Microfluidics

Abstract: In the present study we demonstrate highly sensitive detection of rare, aberrant cells in a population of wild-type human cells by combining a rolling circle-enhanced enzyme activity single molecule detection assay with a custom designed microfluidic device. Besides reliable detection of low concentrations of aberrant cells, the integrated system allowed multiplexed detection of individual enzymatic events at the single cell level. The single cell sensitivity of the presented setup relies on the combination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 25 publications
(60 reference statements)
0
43
0
Order By: Relevance
“…Inspired by our previous finding that chemical reaction appears to be relatively more efficient in small microincubators than in large volume (such as in eppendorf tube) [9,10], we tested the enzyme extraction efficiency in microdroplets based extraction. As evident in Figure 3a, more signals, indicating higher enzymatic activity, was preserved from the microdroplets-based extraction, compared to the bead-beating lysis and bulk mixing.…”
Section: Resultsmentioning
confidence: 99%
“…Inspired by our previous finding that chemical reaction appears to be relatively more efficient in small microincubators than in large volume (such as in eppendorf tube) [9,10], we tested the enzyme extraction efficiency in microdroplets based extraction. As evident in Figure 3a, more signals, indicating higher enzymatic activity, was preserved from the microdroplets-based extraction, compared to the bead-beating lysis and bulk mixing.…”
Section: Resultsmentioning
confidence: 99%
“…26 Droplets of water in oil not only allow for the accumulation of products of single-cell enzymatic reactions in the same compartment as the genome but also provide an opportunity for the amplified detection of single enzymatic events from single cells. 96 In a recently reported assay, rolling circle amplification serves as an amplification method and empowers the detection of single DNA cleavage-ligation events. 96 Moreover, droplet microfluidics allows for fast screening of large libraries (10 8 in 10 h), 97 and studies focusing on the binding affinity of proteins have shown that the size of the library screened is correlated with the improvement achieved in the affinity of the selected proteins.…”
Section: Evolution Of Microorganisms In Dropletsmentioning
confidence: 99%
“…96 In a recently reported assay, rolling circle amplification serves as an amplification method and empowers the detection of single DNA cleavage-ligation events. 96 Moreover, droplet microfluidics allows for fast screening of large libraries (10 8 in 10 h), 97 and studies focusing on the binding affinity of proteins have shown that the size of the library screened is correlated with the improvement achieved in the affinity of the selected proteins. 98 Similarly, these types of correlations are also expected in studies on enzymes.…”
Section: Evolution Of Microorganisms In Dropletsmentioning
confidence: 99%
“…Two syringe pumps (Harvard Apparatus, Holliston, MA, USA) were used to control the flow rates of oil/surfactant and reagents independently. The droplet volume and generation frequency were controlled by the flow rate ratio, determined by the competition between continuous phase and disperse phase [2,6,7]. Subsequently, blood and lysis buffer (10 mM Tris pH 7.5, 5 mM EDTA supplemented with protease inhibitors) were subjected to droplet microfluidics essentially as described previously [2].…”
Section: Enzyme Extraction Using Droplet Microfluidicsmentioning
confidence: 99%